Research on Fresh Produce Sales Prediction Algorithm for Store Based on Multidimensional Time Series Data Analysis - Li, Zhiyu; Yu, Wei; Zhu, Wenwei; Wan, Haojie; Peng, Jingjing; Wang, Hui (EAI Endorsed Transactions on Scalable Information Systems, 2023)
INTRODUCTION: Fresh produce is a daily necessity; however, offline stores often rely on personal experience for purchase, which is highly subjective and may result in inaccurate estimation of purchase quantities. This can lead to produce wastage and subsequently impact the profitability of business. This paper introduces a fresh produce sales prediction model, which can predict fresh produce sales by analyzing multidimensional time series data that influence sales. This model aims to provide guidance for fresh produce purchase in offline stores.OBJECTIVES: The purpose of this study is to predict fresh produce sales by analyzing multidimensional time series data that influence sales. This aims to provide a basis for fresh produce purchase in stores, reduce produce wastage, and enhance business profitability.METHODS: This paper proposes a fresh produce sales prediction model by analyzing multidimensional time series data that affect store sales of fresh produce. An essential component of this model is the ARIMA-LSTM combined prediction model. In this study, the weighted reciprocal of errors averaging method is selected as the weight determination method for the ARIMA-LSTM combined prediction model.RESULTS: In this paper, the ARIMA-LSTM combined model is used for prediction in two scenarios: when the single-model prediction accuracy is superior and when it is inferior. Experimental results indicate that in the case of lower accuracy in single-model prediction, the combined prediction model outperforms, improving prediction accuracy by 3.86% as measured by MAPE. Comparative experiments are conducted between the fresh produce sales prediction model proposed in this paper and time series prediction framework Prophet, traditional LSTM model, and ARIMA model. The experimental results indicate that the proposed model outperforms the others.CONCLUSION: The fresh produce sales prediction model proposed in this paper is based on multidimensional time series data to predict fresh produce sales in stores. This model can accurately predict the sales of fresh produce, providing purchase guidance for fresh produce stores, reducing fresh produce wastage caused by subjective purchasing factors, and increase business profits.
Keywords: Fresh produce sales prediction; Multidimensional time series data; Combined prediction model; LSTM